Emerging treatments in neurogastroenterology: a multidisciplinary working group consensus statement on opioid‐induced constipation. Issue 10 (28th August 2014) - Camilleri, M.; Drossman, D. A.; Becker, G.; Webster, L. R.; Davies, A. N.; Mawe, G. M.
Abstract Background Opioids are effective for acute and chronic pain conditions, but their use is associated with often difficult‐to‐manage constipation and other gastrointestinal (GI) effects due to effects on peripheral μ‐opioid receptors in the gut. The mechanism of opioid‐induced constipation (OIC) differs from that of functional constipation (FC), and OIC may not respond as well to most first‐line treatments for FC. The impact of OIC on quality of life (QoL) induces some patients to decrease or stop their opioid therapy to relieve or avoid constipation. Purpose At a roundtable meeting on OIC, a working group developed a consensus definition for OIC diagnosis across disciplines and reviewed current OIC treatments and the potential of treatments in development. By consensus, OIC is defined as follows: 'A change when initiating opioid therapy from baseline bowel habits that is characterized by any of the following: reduced bowel movement frequency, development or worsening of straining to pass bowel movements, a sense of incomplete rectal evacuation, or harder stool consistency'. The working group noted the prior validation of a patient response outcome and end point for clinical trials and recommended future efforts to create treatment guidelines and QoL measures specific for OIC. Details from the working group's discussion and consensus recommendations for patient care and research are presented in this article.